2019
DOI: 10.1186/s12874-018-0645-0
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of patient-reported complications following hip or knee arthroplasty procedures

Abstract: BackgroundPatient reported outcomes are increasingly used to assess the success of surgical procedures. Patient reported complications are often included as an outcome. However, these data must be validated to be accurate and useful in clinical practice.MethodsThis was a retrospective descriptive study of 364 patients who had completed their six-month follow-up review questionnaire in the Arthroplasty Clinical Outcomes Registry, National (ACORN), an Australian orthopaedic registry. Patient-reported complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Conversely, patients appeared to more accurately report the absence of complications with high NPV and specificity values observed. Our data is in keeping with an Australian registry study that demonstrated patients more accurately report the absence of complications but not the presence [15].…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, patients appeared to more accurately report the absence of complications with high NPV and specificity values observed. Our data is in keeping with an Australian registry study that demonstrated patients more accurately report the absence of complications but not the presence [15].…”
Section: Discussionsupporting
confidence: 89%
“…Literature review, however, has shown that the nursing staff for rehabilitation services is insufficient and that patients undergoing home-based rehabilitation receive inadequate guidance. More than 56% of elderly patients who have undergone hip replacement [10–12] have experienced diverse problems, such as persistent dysfunction, joint stiffness, and pulmonary infection due to improper home-based rehabilitation after discharge. Previous study[13] has validated the program theory of the Groningen orthopaedic exit strategy (GOES), a theory-driven program aiming to improve the rehabilitation of total hip and knee arthroplasty patients after shortened hospital stay, and has found that the conceptual theory is supported; however, as the treatment did not influence the mediating variables (action theory), the value was very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Additional outcomes include healthcare use, such as clinic visits, acute care evaluations, hospital admissions and secondary procedures. These outcomes will be ascertained by a patient or caregiver self-report and abstraction from the EHR 33–35. Centers for Disease Control and Prevention definitions for nosocomial urinary tract infections and multidrug resistant organisms will be used 36 37…”
Section: Methodsmentioning
confidence: 99%